2020
DOI: 10.3390/pharmaceutics12080759
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Virus-Derived Nanosystems (SVNs) for Delivery and Precision Docking of Large Multifunctional DNA Circuitry in Mammalian Cells

Abstract: DNA delivery is at the forefront of current research efforts in gene therapy and synthetic biology. Viral vectors have traditionally dominated the field; however, nonviral delivery systems are increasingly gaining traction. Baculoviruses are arthropod-specific viruses that can be easily engineered and repurposed to accommodate and deliver large sequences of exogenous DNA into mammalian cells, tissues, or ultimately organisms. These synthetic virus-derived nanosystems (SVNs) are safe, readily customized, and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Nevertheless, a lot of effort is being made to overcome the limitations (Aulicino et al 2020) that other viral vectors used in gene therapy do not escape, where those vectors can generate much greater immune responses as a result of being derived from mammalian pathogens and have other serious disadvantages including the limited duration of the transgenes they carry and the costs of scaled-up production. Thus, several investigations have been reported that have offered improvements in baculoviral vectors for BacMamtype applications.…”
Section: Bacmam Technology Associated With Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a lot of effort is being made to overcome the limitations (Aulicino et al 2020) that other viral vectors used in gene therapy do not escape, where those vectors can generate much greater immune responses as a result of being derived from mammalian pathogens and have other serious disadvantages including the limited duration of the transgenes they carry and the costs of scaled-up production. Thus, several investigations have been reported that have offered improvements in baculoviral vectors for BacMamtype applications.…”
Section: Bacmam Technology Associated With Gene Therapymentioning
confidence: 99%
“…In the coming years, owing to the development of more extensive knowledge about baculoviruses, which new perspective will enable the development of the next generation of vectors for producing better-engineered virions that would be more useful for the aforementioned applications and for other innovations, we could expect that these technologies will be well valued by and appropriate for more human-and veterinary-health companies. Furthermore-and in view of the approvals received in recent years by various humangene-therapy products based on viral vectors (Ginn et al 2018) and the new generation of vaccines that use virions (Rawat et al 2021)-we would expect that in this third decade of the twenty-first century, clinical trials in humans may begin to promote BacMam technologies and bring those procedures to the pharmaceutical market (Aulicino et al 2020). The usefulness of the application of baculoviruses in human and animal health is already indisputable.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Scale bars (50 μm) are drawn in white (adapted from Sari-Ak et al, 2019). genetic code expansion (Koehler et al, 2016), or multifunctional DNA delivery in mammalian and human cells and tissues, among others (Aulicino, Capin, & Berger, 2020;Mansouri et al, 2016;Sari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has also allowed us to realize that what is seen with SARS-CoV-2 is a form of nanotoxicity and that several new tools such as artificial intelligence have been deployed to understand the disease and develop therapies to combat it (Ahuja et al, 2020;Shaker et al, 2020). Therefore, similar tools should be used in the design of future nanotoxicology studies but also in the development of bioinspired drug delivery systems like viruses (Aulicino et al, 2020).…”
Section: Toxicity Of Covid-19 On Different Cells and The Need For Relmentioning
confidence: 99%